ChemInform Abstract: Direct Alkynylation of 3H‐Imidazo[4, 5‐b]pyridines Using gem‐Dibromoalkenes as Alkynes Source. Issue 41 (September 2016) - Aziz, Jessy; Baladi, Tom; Piguel, Sandrine
Abstract: The method presented is highly efficient in the presence of either CuBrSMe2 [cf.